2011
DOI: 10.1016/j.ijhm.2010.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Towards Strategic Intent: Perceptions of disability service provision amongst hotel accommodation managers

Abstract: a b s t r a c tThe tourism sector globally has become increasingly mindful of how an ageing population is reshaping service provision forms and offerings. This being particularly true of accommodation operations where there is a now a growing recognition of the commercial value for providing market groups with exceptional service. With this in mind, this study sought to ascertain the perceptions of managers in the accommodation sector towards disability service provision with a view to identifying any current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
1
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 129 publications
(94 citation statements)
references
References 29 publications
3
81
1
9
Order By: Relevance
“…For example, Buhalis and Omar MOUFAKKIR : Toward a better tourism enjoyment for tourists with disabilities Michopoulou (2011) used focus groups to assess website accessibility for people with disabilities. Darcy and Pegg (2010) used both interviews and focus groups to study the perceptions of disability service delivery among hotel accommodation managers. Freeman and Selmi (2010) interviewed people with disabilities to understand their flight experience.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, Buhalis and Omar MOUFAKKIR : Toward a better tourism enjoyment for tourists with disabilities Michopoulou (2011) used focus groups to assess website accessibility for people with disabilities. Darcy and Pegg (2010) used both interviews and focus groups to study the perceptions of disability service delivery among hotel accommodation managers. Freeman and Selmi (2010) interviewed people with disabilities to understand their flight experience.…”
Section: Methodsmentioning
confidence: 99%
“…A review of the literature (e.g. Yau et al, 2004;Michopoulou and Buhalis, 2013;Darcy and Pegg, 2010;Buhalis and Michopoulou, 2011;Freeman and Selmi, 2010;Poria et al, 2010) identified key themes, issues, and questions to focus on. Specifically, the study considered a set of questions, including information about trip constraints and trip enjoyment.…”
Section: Résumé De L'articlementioning
confidence: 99%
See 3 more Smart Citations